HEPATOMA-ASSOCIATED NON-ISLET CELL TUMOR HYPOGLYCEMIA: A CASE REPORT - Oon, Jen Hoong; Ho, Yon Li; Tong, Chin Voon; Tob, Noor Hafis Md; Lee, Siow Ping; Vergis, Melissa (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Non-islet cell tumour hypoglycaemia (NICTH) is a rare condition due to excessive secretion of insulin-like growth factor-2 (IGF-2) or pro-IGF-2. NICTH is commonly associated with hepatocellular carcinomas. CASE We reviewed case notes, investigation results, imaging studies and discussed treatment options based on literature review. A 73-year-old Chinese male with a history of type 2 diabetes mellitus, hypertension and stage IV chronic kidney disease presented to emergency department with syncope attack and capillary blood glucose of 1.9 mmol/L. Initial examination revealed massive hepatomegaly. A 4-phase CT scan of the liver showed multicentric hepatocellular carcinoma. Biochemical investigations revealed hypoinsulinaemic hypoglycaemia, elevated alfafetoprotein (AFP) at 135,937 IU/mL, markedly suppressed insulin-like growth factor-1 (IGF-1) and normal IGF-2 level. The IGF-2: IGF-1 ratio was 50:1. He was started on oral prednisolone, titrated up to 25mg twice daily to maintain euglycemia. After discussion with surgical and oncology teams, patient opted for conservative management. Elevated IGF-2 or pro-IGF-2 exerts insulin mimicking effects leading to hypoglycaemia. The diagnosis of NICTH is based on the IGF-2: IGF-1 ratio, which is higher than 10:1, along with inappropriately suppressed IGF-1. Curative treatment for NICTH is complete resection of the tumour. Glucocorticoids is important to maintain euglycemia on top of nutritional support and glucose infusion. Glucagon has a limited role as adjunct therapy. Diazoxide and octreotide were found ineffective. CONCLUSION This is a case of hepatoma-associated NICTH, which was managed with oral prednisolone to maintain euglycemia. Due to advanced disease, we were unable to deliver definitive treatment. High level of suspicion of NICTH is crucial in patients with recurrent hypoglycaemia on a background of malignancy.